Integrated Group Investigation Model Impact on Students’ Writing Achievement - Meikardo Samuel Prayuda (Kampret Journal, 2023)
This research was purposed to find out if integrated group investigation model could give significance impact to the students’ writing achievement. The instruments that used in this study was tests. The tests were divided into two, there were pre-test and post test. Both test consisted of 1 item. In this study, the study applied the pre-test in both control and experiment groups. After that, the study applied the teaching process by using group investigation model in experiment class and conventional way in control class. After the teaching process finished, the study took the data of the post-test. In the pre-test, the data showed that the students’ achievement in writing was low, both in control and experiment classes. The result was the students writing achievement in control class got 54.66mean score and in experiment class the students got 60.00 mean score both in pre-tests. Then, the researcher conduct the study with the students in control class taught by using conventional way and students in experiment class taught by using group investigation model. When the post-test was given to each class, the result was the students in control class got 71.00 mean score and students in experiment class got 87.66 mean score. From the data, it could be concluded that teaching writing by using group investigation model could give significance effect to the students’ writing achievement